2022
DOI: 10.3389/fneur.2022.918086
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Fingolimod-Associated Macular Edema

Abstract: ObjectiveTo investigate the clinical features, treatment, and prognosis of fingolimod-associated macular edema (FAME) and to provide a reference for its rational management.MethodsFAME-related case reports were included in a pooled analysis by searching Chinese and English databases from 2010 to November 31, 2021.ResultsThe median age of 41 patients was 50 years (range, 21, 67 years), of whom 32 were women. The median time to onset of FAME was 3 m (range.03, 120), and blurred vision (17 cases) and decreased vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous studies of FAME, which is physiologically similar to PAME, have shown prompt resolution after sub-Tenon corticosteroid injection, a treatment that can be considered in the setting of refractory or difficult-to-treat macular edema. 6,8 An alternate approach to treating our asymptomatic patient could have been to closely monitor her while continuing the ponesimod. An intervention could have then been made with topical medication, a sub-Tenon corticosteroid, and/or cessation of ponesimod if the PAME worsened or she developed visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of FAME, which is physiologically similar to PAME, have shown prompt resolution after sub-Tenon corticosteroid injection, a treatment that can be considered in the setting of refractory or difficult-to-treat macular edema. 6,8 An alternate approach to treating our asymptomatic patient could have been to closely monitor her while continuing the ponesimod. An intervention could have then been made with topical medication, a sub-Tenon corticosteroid, and/or cessation of ponesimod if the PAME worsened or she developed visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients beginning ponesimod therapy should receive a pretreatment ophthalmic evaluation, including macular OCT scans as well as regular monitoring during the treatment course-a suggestion maintained by the US Food and Drug Administration for the less S1P 1 R-selective fingolimod and recommended by Janssen's ponesimod prescribing information. 8,11 Patients should further be informed that any painless vision loss during treatment requires urgent evaluation by their ophthalmologist. If macular edema is noted, transitioning patients from ponesimod treatment and starting supportive topical therapy with corticosteroids and NSAIDs is an effective PAME management algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The iBRB, which regulates the movement of solutes from the retinal vasculature to the neuroretina, is composed of tight junctions located between retinal vascular endothelial cells, regulated by perivascular astrocytes, pericytes, and Müller cells. S1PR 1 was found highly expressed in endothelial cells and it is believed to play a role in the correct functioning of the intercellular tight junctions (4,5). Thus, siponimod may modulate S1PR1 on endothelial cells, resulting in the internalization of the receptors, transient dysfunction of the iBRB and impairment of retinal hydric homeostasis leading to intraretinal edema and foveal detachment.…”
mentioning
confidence: 99%